Correlation of Pharyngeal Residue with PenetrationAspiration in Post-Radiotherapy Nasopharyngeal Carcinoma Patients with Oropharyngeal Dysphagia (Medico Legal Update, 2021)
Background: Nasopharyngeal carcinoma (NPC) ranks first for head and neck malignancies, and radiotherapyis a recommended treatment. Most post-radiotherapy NPC patients experience oropharyngeal dysphagia thatresults in pharyngeal residue. Pharyngeal residue is thought to be a risk factor for aspiration-penetration.Objective: Examining the correlation between pharyngeal residue and penetration-aspiration in postradiotherapy NPC patients.Method: Participants have been identified since 2018 to find out the total number of NPC patients. Inthe period January-October 2019, identification of NPC patients was performed according to participantcriteria. Participants were examined for fiberoptic endoscopic evaluation of swallowing (FEES), pharyngealresidue using the Yale Pharyngeal Residue Severity Rating Scale (YPR-SRS), and penetration-aspirationusing Penetration-Aspiration Scale (PAS). Statistical tests were used Spearman correlation test with p